Waterproof flame-retardant cable material and preparation method thereof

By modifying magnesium hydroxide and combining co-effective flame retardant, the problem of difficult to balance the flame retardant performance and waterproof performance of cable materials is solved, and the comprehensive performance of cable materials is improved, and the application prospects for adapting to specific environmental conditions are broad.

CN119823460APending Publication Date: 2025-04-15YANGZHOU HUASHENG ELECTRONICS IND
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411802768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

It is difficult to balance existing cable materials between flame retardant properties and waterproof properties, and the flame retardant is unevenly dispersed in the matrix, affecting the mechanical properties of the material.

Method used

By modifying magnesium hydroxide, polyester compounds are used to improve their compatibility with polymer matrix, and a synergistic effect is formed with synergistic flame retardant and antimony trioxide, thereby improving the flame retardant and waterproofing properties of cable materials.

Benefits of technology

It has achieved the synchronous improvement of the flame retardant performance and waterproof effect of cable materials, enhanced its mechanical properties and aging resistance, adapted to specific environmental conditions, and had broad market application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823460A_ABST
    Figure CN119823460A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of compositions of high-molecular compounds, in particular to a waterproof flame-retardant cable material and a preparation method thereof. The cable material comprises the following components in parts by weight: 80-110 parts of polyethylene, 10-30 parts of modified magnesium hydroxide, 40-60 parts of talcum powder, 1-2 parts of antimony trioxide, 4-6 parts of a synergistic flame retardant, 35-45 parts of heavy calcium carbonate, 15-25 parts of carbon black, 3-6 parts of an anti-aging agent, 2-6 parts of a plasticizer and 1-5 parts of a lubricant. The invention also provides a preparation method of the composition. Compared with the prior art, the prepared cable material has the advantages of being good in flame retardant effect, waterproof performance and mechanical performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer compound compositions, and in particular to a waterproof and flame-retardant cable material and a preparation method thereof. Background Art

[0002] Cable materials are materials used for insulation and sheathing of wires and cables. There are many types of cable materials, including PVC cable materials, rubber cable materials, polyethylene cable materials, etc. The performance of cable materials directly affects the electrical properties, mechanical properties and safety of use of cables. With the development of economy and the advancement of science and technology, the performance requirements of cable materials are also constantly improving, especially in terms of flame retardancy, waterproofness, environmental protection, etc. Traditional cable materials, such as polyvinyl chloride (PVC) cable materials, although low in price and excellent in performance, will release a lot of smoke and toxic gases when burned, causing harm to the environment and human health. Therefore, people began to seek more environmentally friendly and safer alternatives to cable materials. Low-smoke halogen-free flame-retardant cable materials were developed in this context. This type of cable material produces less smoke when burned and does not contain halogen, thereby reducing the harm to the environment and human body. It is usually prepared by melt blending with high-density polyethylene (HDPE) and ethylene-vinyl acetate copolymer (EVA) as the base material, adding surface-modified magnesium hydroxide as filler, and red phosphorus as a flame retardant. Studies have shown that when the ratio of EVA / HDPE and the dosage of magnesium hydroxide and red phosphorus are appropriate, the resulting cable material has good physical and mechanical properties and excellent flame retardant properties, which can meet the needs of actual production.

[0003] The emergence of waterproof and flame-retardant cable materials is to solve the limitations of traditional cable materials in special environments, such as poor flame retardancy, easy deformation at high temperature, poor mechanical properties, poor waterproof performance and short service life. This cable material combines the advantages of raw materials such as tetrafluoroethylene rubber, EPDM rubber and chlorinated polyethylene, improves the performance of traditional cable materials, and makes it have excellent mechanical properties and low permeability, as well as waterproof and moisture-proof properties. In addition, by adding carbonizing agents, reinforcing agents, flame retardants, antioxidants and lubricants, the waterproof and moisture-proof, flame retardant and aging resistance of the cable are further enhanced, making the cable material smoother and more delicate in appearance.

[0004] CN106519521A discloses a waterproof and flame-retardant cable material, which is made of the following raw materials in parts by weight: 30-60 parts of tetrafluoroethylene rubber, 25-40 parts of ethylene propylene rubber, 20-35 parts of chlorinated polyethylene, 10-30 parts of ammonium polyphosphate, 10-20 parts of kaolin, 20-30 parts of nano carbon black, 1-5 parts of sulfur, 15-30 parts of flame retardant, 1-5 parts of antioxidant and 1-5 parts of lubricant. The invention also discloses a method for preparing a waterproof and flame-retardant cable material. The preparation method of the cable material of the invention is simple and easy to operate; it has the characteristics of being waterproof and moisture-proof, as well as flame retardant and aging-resistant, and the product has a smooth and delicate appearance; it can adapt to specific environmental conditions of use, and has broad market application prospects.

[0005] CN118725444A discloses a method for preparing a high-strength halogen-free flame-retardant overhead cable material, which belongs to the technical field of cable materials. The raw materials of the overhead cable material include: 60-80 parts of ethylene-vinyl acetate copolymer, 10-20 parts of inorganic filler, 5-10 parts of maleic anhydride grafted ethylene-vinyl acetate copolymer, 5-12 parts of flame retardant, 1-3 parts of coupling agent, 0.6-0.8 parts of lubricant, 0.5-1 parts of antioxidant, 0.5-1 parts of ultraviolet absorber, and 0.1-0.2 parts of cross-linking auxiliary agent. The flame retardant of the invention is a PN synergistic flame retardant system, and it also contains rich fluorine atoms. In addition, the flame retardant, filler and matrix material form a three-dimensional network structure, so that the flame retardant and filler of the invention can be stably present in the cable material for a long time, so the cable material of the invention has efficient and safe flame retardant effect, waterproof and moisture-proof effect, and in addition to the effects of other raw materials, the cable material also has excellent thermal stability, aging resistance and other properties.

[0006] With the increasing number of power cable fire incidents, the society's demand for power cables with flame retardant properties is growing. Traditional halogen-containing flame retardant cables, such as polyvinyl chloride (PVC) cable materials, easily release toxic gases and thick smoke during combustion, posing a serious threat to human health and the natural environment. Therefore, the development of halogen-free flame retardant polyolefin power cables has become very urgent, and this has also become a hot area of ​​research. Among the base materials of halogen-free flame retardant polyolefin cable materials, materials such as polyethylene (PE), polypropylene (PP) and ethylene-vinyl acetate copolymer (EVAC) are widely used. However, it is difficult for halogen-free flame retardant polyolefin cable materials to achieve an ideal balance between electrical properties, mechanical properties and flame retardant properties. Therefore, improving the comprehensive performance of halogen-free flame retardant polyolefin cable materials by modification or compounding has become one of the key directions of current research. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a waterproof and flame-retardant cable material and a preparation method thereof.

[0008] The addition of flame retardants may cause uneven dispersion in the matrix, leading to agglomeration and an increase in the number of defects, which is very unfavorable to the mechanical properties of the material. How to appropriately modify the composite system of the matrix and flame retardant and improve the compatibility of the matrix and flame retardant to achieve simultaneous improvement of mechanical properties and flame retardant properties is the current research focus in this field. Hydroxide flame retardants have poor compatibility with polymer matrices, and the mass fraction of added fillers usually exceeds 50%, which will cause serious damage to the mechanical properties of the composite material. Surface treatment is the use of physical or chemical methods to treat the surface of the flame retardant, thereby improving the compatibility of the flame retardant and the polymer matrix and the comprehensive performance of the composite material. The present invention provides a modified magnesium hydroxide, wherein the modified magnesium hydroxide is modified by a prepared polyester compound to obtain the modified magnesium hydroxide. Since the ester group and the alkyl side chain of the polyester compound are lipophilic and hydrophobic, the modified magnesium hydroxide has better compatibility with the polymer matrix, and can also enhance the waterproofness of the final cable material. The multiple aromatic rings in the polyphenol compound can further enhance the flame retardant properties of magnesium hydroxide as an inorganic flame retardant, and the mechanical properties brought by the aromatic ring as a rigid group. The addition of a synergistic flame retardant can form a synergistic effect with antimony trioxide, thereby further enhancing the flame retardant properties. The modified magnesium hydroxide is applied to the cable material to finally prepare a cable material with excellent flame retardant properties and waterproof effects, which can adapt to specific use environment conditions and has broad market application prospects.

[0009] To achieve the above-mentioned purpose, the present invention provides a waterproof and flame-retardant cable material, comprising the following components in parts by weight: 80-110 parts of polyethylene, 10-30 parts of modified magnesium hydroxide, 40-60 parts of talc, 1-2 parts of antimony trioxide, 4-6 parts of synergistic flame retardant, 35-45 parts of heavy calcium carbonate, 15-25 parts of carbon black, 3-6 parts of antioxidant, 2-6 parts of plasticizer and 1-5 parts of lubricant.

[0010] The preparation method of the modified magnesium hydroxide comprises the following steps:

[0011] X1. Mix terephthalaldehyde, 2,5-didodecylphenol and p-toluenesulfonic acid, heat and stir for 2-3 hours, cool to room temperature, add water and ethanol to produce precipitation, stir for 4-8 hours and filter, dry the filter cake and mix with acetic anhydride and sulfuric acid, stir at 60-70°C for 4-6 hours, cool and add water to produce precipitation, filter, and dry the filter cake to obtain a polyester compound;

[0012] X2. Add magnesium hydroxide to ethanol and disperse it evenly. Then add ethanol solution of polyester compound. The mass ratio of magnesium hydroxide to polyester compound is 1:2-3. Stir for 20-30 hours, irradiate with ultrasonic wave for 0.2-1 hour and filter. Wash the filter cake with ethanol for 2-4 times to obtain modified magnesium hydroxide.

[0013] Furthermore, the molar ratio of terephthalaldehyde to 2,5-didodecylphenol and p-toluenesulfonic acid is 1:4-5:0.1-0.2.

[0014] Furthermore, the temperature range of the heating in step X1 is 80-90°C.

[0015] Furthermore, the molar ratio of the filter cake to acetic anhydride and sulfuric acid after drying is 1:5-10:0.1-0.2.

[0016] Furthermore, the concentration of the polyester compound ethanol solution is 1 to 5 wt %.

[0017] Furthermore, the preparation method of the modified magnesium hydroxide comprises the following steps:

[0018] X1. Mix terephthalaldehyde, 2,5-didodecylphenol and p-toluenesulfonic acid, heat to 80-90°C and stir for 2-3h. The molar ratio of terephthalaldehyde, 2,5-didodecylphenol and p-toluenesulfonic acid is 1:4-5:0.1-0.2. After cooling to room temperature, add water and ethanol to produce a precipitate. Stir for 4-8h and filter. After drying the filter cake, mix with acetic anhydride and sulfuric acid in a molar ratio of 1:5-10:0.1-0.2, stir at 60-70°C for 4-6h, cool and add water to produce a precipitate. Filter and dry the filter cake to obtain a polyester compound.

[0019] X2. Add magnesium hydroxide to ethanol and disperse it evenly. Then add 1-5wt% ethanol solution of polyester compound and diglycidyl ether. The mass ratio of magnesium hydroxide to polyester compound and diglycidyl ether is 1:2-3:0.05-0.2. Stir for 20-30 hours, irradiate with ultrasonic wave for 0.2-1 hour and filter. Wash the filter cake with ethanol for 2-4 times to obtain modified magnesium hydroxide.

[0020] Furthermore, the talcum powder has a particle size of 50% distributed between 4 and 6 μm, a hydrochloric acid insoluble matter of ≥85%, and a magnesium oxide content of ≥30%.

[0021] Furthermore, the antimony trioxide has an antimony trioxide content greater than 99.8%, and a 325-mesh sieve residue of ≤0.1%.

[0022] Furthermore, the synergistic flame retardant is one of zinc borate, nano-montmorillonite, silicate, and red phosphorus.

[0023] Furthermore, the heavy calcium carbonate has a calcium carbonate content greater than 98% and an oil absorption value of 33.0 to 43.0 g / 100 g.

[0024] Furthermore, the carbon black has a sieve residue (325 μm) of ≤0.5%.

[0025] Furthermore, the antioxidant is one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 4,4'-bis(α,α-dimethylbenzyl) diphenylamine or 2,2,4-trimethyl-1,2-dihydroquinoline polymer.

[0026] Furthermore, the plasticizer is one of phthalate esters, aliphatic dibasic acid esters and polyol esters.

[0027] Furthermore, the lubricant is one of stearic acid, paraffin, polyethylene wax, and zinc stearate.

[0028] A method for preparing a waterproof and flame-retardant cable material comprises the following steps:

[0029] The components in the formula are blended, fully mixed, melt blended and then extruded and granulated to obtain the waterproof and flame-retardant cable material.

[0030] Beneficial effects of the present invention:

[0031] Compared with the prior art, the present invention provides a modified magnesium hydroxide, which is obtained by modifying magnesium hydroxide with a prepared polyester compound. Since the ester group and alkyl side chain of the polyester compound are lipophilic and hydrophobic, the modified magnesium hydroxide has better compatibility with the polymer matrix, and can also enhance the waterproofness of the final cable material. The multiple aromatic rings in the polyphenol compound can further enhance the flame retardant properties of magnesium hydroxide as an inorganic flame retardant, and the mechanical properties brought by the aromatic ring as a rigid group. The modified magnesium hydroxide is applied to the cable material to finally prepare a cable material with excellent flame retardant and waterproof effects, which can adapt to specific use environment conditions and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Product pictures prepared for cable materials.

[0033] Figures 2-3 This is the factory inspection report for cable materials. DETAILED DESCRIPTION

[0034] 2,5-didodecylphenol, CAS No.: 1115234-59-7.

[0035] Diglycidyl ether, CAS number: 2238-07-5.

[0036] Polyethylene, HDPE DGDX-6095, Dushanzi Petrochemical.

[0037] In the present invention, polyethylene, modified magnesium hydroxide, talcum powder, antimony trioxide, zinc borate, heavy calcium carbonate, carbon black, pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], dinonyl phthalate and polyethylene wax are blended, fully mixed and uniformly mixed, and then melt blended and extruded and granulated to obtain a waterproof and flame-retardant cable material, wherein polyethylene is used as a basic material and a main component to provide basic physical properties of the cable material, such as flexibility, chemical resistance and electrical insulation. The content of polyethylene is 80 to 110 parts, which is the main component in the formula. Modified magnesium hydroxide, as an inorganic flame retardant, has the triple functions of filling, flame retardant and smoke suppression. It can improve the flame retardant properties of the material and reduce the generation of smoke and toxic gases during combustion. Talc powder is used as a filler to improve the mechanical strength and heat resistance of the material while reducing the cost. Antimony trioxide and synergistic flame retardant are used to enhance the flame retardant effect of magnesium hydroxide. Heavy calcium carbonate is used as a filler to increase the rigidity and heat resistance of the material while reducing the cost. Carbon black improves the conductivity and antistatic properties of the material and acts as an auxiliary flame retardant. Antioxidants prevent thermal and oxidative aging of the material during processing and use, extending the service life of the material. Plasticizers improve the flexibility and processing properties of the material. Lubricants improve the processing properties of the material and reduce friction and wear during processing. The surface of magnesium hydroxide is modified to improve its dispersibility and compatibility in the polymer matrix, thereby improving the flame retardant properties. This modified magnesium hydroxide can more effectively improve the flame retardant properties of cable materials while reducing the impact on the properties of the polymer matrix.

[0038] Example 1

[0039] A method for preparing a waterproof flame-retardant cable material comprises the following steps, measured in parts by weight:

[0040] 100 parts of polyethylene, 20 parts of modified magnesium hydroxide, 50 parts of talc, 2 parts of antimony trioxide, 5 parts of red phosphorus, 40 parts of heavy calcium carbonate, 20 parts of carbon black, 4 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 5 parts of dinonyl phthalate and 2 parts of polyethylene wax are blended, mixed thoroughly and uniformly, and then melt-blended and extruded and granulated to obtain a waterproof and flame-retardant cable material.

[0041] The preparation method of the modified magnesium hydroxide comprises the following steps:

[0042] X1. Mix terephthalaldehyde, 2,5-didodecylphenol and p-toluenesulfonic acid in a molar ratio of 1:4:0.15, heat to 85°C and stir for 3 hours, cool to room temperature, add 10 times the volume of water and 3:2 of ethanol mixture, precipitate appears, stir for 6 hours, filter, dry the filter cake, mix with acetic anhydride and sulfuric acid in a molar ratio of 1:8:0.1, stir at 65°C for 6 hours, cool, add 10 times the volume of water, precipitate appears, filter, and dry the filter cake to obtain a polyester compound;

[0043] X2. Add magnesium hydroxide to 10 times the volume of ethanol and disperse it evenly. Then add 2.5wt% ethanol solution of polyester compound, the mass ratio of magnesium hydroxide to polyester compound is 1:2.5. Stir for 24 hours, irradiate with ultrasonic wave for 0.5 hours and then filter. Wash the filter cake with ethanol for 3 times to obtain modified magnesium hydroxide.

[0044] Example 2

[0045] The method is substantially the same as Example 1, except that the amount of modified magnesium hydroxide is 15 parts.

[0046] Example 3

[0047] The method is substantially the same as Example 1, except that the amount of modified magnesium hydroxide is 25 parts.

[0048] Example 4

[0049] The method is substantially the same as Example 1, except that the amount of modified magnesium hydroxide is 30 parts.

[0050] Example 5

[0051] It is basically the same as Example 1, the only difference being that red phosphorus is replaced by zinc borate.

[0052] Example 6

[0053] It is basically the same as Example 1, the only difference being that the red phosphorus is replaced by nano-montmorillonite.

[0054] Example 7

[0055] It is basically the same as Example 1, the only difference being that red phosphorus is replaced by calcium silicate.

[0056] Example 8

[0057] 100 parts of polyethylene, 20 parts of modified magnesium hydroxide, 50 parts of talc, 2 parts of antimony trioxide, 5 parts of red phosphorus, 40 parts of heavy calcium carbonate, 20 parts of carbon black, 4 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 5 parts of dinonyl phthalate and 2 parts of polyethylene wax are blended, mixed thoroughly and uniformly, and then melt-blended and extruded and granulated to obtain a waterproof and flame-retardant cable material.

[0058] The preparation method of the modified magnesium hydroxide comprises the following steps:

[0059] X1. Mix terephthalaldehyde, 2,5-didodecylphenol and p-toluenesulfonic acid in a molar ratio of 1:4:0.15, heat to 85°C and stir for 3 hours, cool to room temperature, add 10 times the volume of water and 3:2 of ethanol mixture, precipitate appears, stir for 6 hours, filter, dry the filter cake, mix with acetic anhydride and sulfuric acid in a molar ratio of 1:8:0.1, stir at 65°C for 6 hours, cool, add 10 times the volume of water, precipitate appears, filter, and dry the filter cake to obtain a polyester compound;

[0060] X2. Add magnesium hydroxide to 10 times the volume of ethanol and disperse it evenly. Then add 2.5wt% ethanol solution of polyester compound and diglycidyl ether. The mass ratio of magnesium hydroxide to polyester compound and diglycidyl ether is 1:2.5:0.1. Stir for 24 hours, irradiate with ultrasonic wave for 0.5 hours and then filter. Wash the filter cake with ethanol for 3 times to obtain modified magnesium hydroxide.

[0061] Comparative Example 1

[0062] A method for preparing a waterproof flame-retardant cable material comprises the following steps, measured in parts by weight:

[0063] 100 parts of polyethylene, 20 parts of magnesium hydroxide, 50 parts of talc, 2 parts of antimony trioxide, 5 parts of red phosphorus, 40 parts of heavy calcium carbonate, 20 parts of carbon black, 4 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 5 parts of dinonyl phthalate and 2 parts of polyethylene wax are blended, mixed thoroughly and uniformly, and then melt-blended and extruded and granulated to obtain a waterproof and flame-retardant cable material.

[0064] Comparative Example 2

[0065] A method for preparing a waterproof flame-retardant cable material comprises the following steps, measured in parts by weight:

[0066] 100 parts of polyethylene, 20 parts of modified magnesium hydroxide, 50 parts of talc, 2 parts of antimony trioxide, 5 parts of red phosphorus, 40 parts of heavy calcium carbonate, 20 parts of carbon black, 4 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 5 parts of dinonyl phthalate and 2 parts of polyethylene wax are blended, mixed thoroughly and uniformly, and then melt-blended and extruded and granulated to obtain a waterproof and flame-retardant cable material.

[0067] The preparation method of the modified magnesium hydroxide comprises the following steps:

[0068] X1. Mix terephthalaldehyde, 2-hydroxy-p-xylene and p-toluenesulfonic acid in a molar ratio of 1:4:0.15, heat to 85°C and stir for 3 hours, cool to room temperature, add 10 times the volume of water and 3:2 of ethanol, and precipitate appears. Stir for 6 hours and filter. After drying the filter cake, mix with acetic anhydride and sulfuric acid in a molar ratio of 1:8:0.1, stir at 65°C for 6 hours, cool, add 10 times the volume of water, and precipitate appears. Filter and dry the filter cake to obtain a polyester compound.

[0069] X2. Add magnesium hydroxide to 10 times the volume of ethanol and disperse it evenly. Then add 2.5% ethanol solution of polyester compound. The mass ratio of magnesium hydroxide to polyester compound is 1:2.5. Stir for 24 hours and irradiate with ultrasonic wave for 0.5 hours. Then filter. Wash the filter cake with ethanol for 3 times to obtain modified magnesium hydroxide.

[0070] Test Example 1

[0071] The tensile properties were tested with reference to GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets". The tensile strength is the maximum tensile stress that the sample bears during the tensile test, and the elongation at break is the tensile strain corresponding to the breaking stress when the sample breaks. The insulation resistance of the cable material at a water temperature of 20°C was tested to characterize the waterproofness. The specific results are shown in Table 1.

[0072] Table 1 Tensile performance test results of waterproof and flame-retardant cable materials

[0073]

[0074]

[0075] As can be seen from Table 1, the cable material prepared by the present invention has good mechanical properties and water resistance, while the mechanical properties and water resistance of Reference Example 1 are obviously poorer than those of Example 1. This may be because magnesium hydroxide is modified in Example 1, and a polyester compound is prepared and then co-precipitated with magnesium hydroxide, and surface modified by intermolecular force. Since the ester group and alkyl side chain of the polyester compound have lipophilic and hydrophobic properties, the modified magnesium hydroxide has better compatibility with the polymer matrix, and the alkyl group diffuses into the interface region of polyethylene, and the molecular chain segments are partially entangled with each other to increase the compatibility of the powder with polyethylene, so that the tensile strain at break of the system will not decrease on a large scale, and the interface enhancement also improves the tensile strength to a certain extent, so the tensile strength and elongation at break of the cable material in Example 1 are higher, and the insulation resistance is lower. However, magnesium hydroxide is not modified in Reference Example 1, and there are many hydroxyls on the surface of magnesium hydroxide, which is easy to agglomerate, and the dispersion degree in the polymer is low, and the compatibility with the polymer is poor, so when used as a flame retardant, it often leads to a significant reduction in mechanical properties. In comparative example 2, magnesium hydroxide was also modified, but the obtained polyester compound had multiple ester groups but no alkyl side chains, so the mechanical properties were improved, but the water resistance was not as good as that in example 1. Compared with examples 2 to 4, the amount of modified magnesium hydroxide used in example 1 was different, which led to differences in mechanical properties, indicating that there was an optimal amount of modified magnesium hydroxide, namely, example 1. Compared with example 1, the mechanical properties and resistance of examples 5 to 7 were not much different, while the mechanical properties and insulation resistance values ​​of example 8 were larger than those of example 1, which may be due to the fact that the introduction of diglycidyl ether can form a cross-linked structure, thereby improving the overall strength, so the tensile strength and elongation at break are further increased, and the further modification of magnesium hydroxide by diglycidyl ether can also improve the water resistance, thereby improving the insulation resistance.

[0076] Test Example 2

[0077] Refer to GB / T2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test" to test the combustion performance and the limiting oxygen index of the cable material. The oxygen index refers to the minimum oxygen concentration that just maintains the combustion of the material when a mixed gas of oxygen and nitrogen at (23±2)℃ is introduced, expressed as a volume fraction. The specific results are shown in Table 2.

[0078] Table 2 Flame retardant performance test results of waterproof flame retardant cable materials

[0079] Experimental protocol Limiting oxygen index / % Example 1 34.2 Example 2 33.3 Example 3 33.7 Example 4 33.9 Example 5 30.1 Example 6 31.2 Example 7 30.6 Example 8 35.0 Comparative Example 1 26.6 Comparative Example 2 27.2

[0080] As can be seen from Table 2, compared with Example 1, the modification of magnesium hydroxide can also improve the flame retardant properties. This is because the surface of unmodified magnesium hydroxide has many hydroxyl groups, which is easy to agglomerate, and the dispersion degree in the resin is low, and the compatibility with the polymer is poor, which even inhibits the flame retardant effect and affects the flame retardant properties of the entire system. The flame retardant property of the composite material is a comprehensive reflection of the synergistic effect between the components of the composite material and the components. The more evenly the flame retardant is dispersed in the composite material, the better the flame retardant property of the composite material; the stronger the force between the flame retardant and the matrix resin, the stronger the heat resistance of the composite material, the ability to resist flames is also improved, and the flame retardant property is also improved. Example 1 Modified magnesium hydroxide is obtained by modifying magnesium hydroxide with the prepared polyester compound. Since the ester group and alkyl side chain of the polyester compound are lipophilic and hydrophobic, the modified magnesium hydroxide has better compatibility with the polymer matrix, and the multiple aromatic rings in the polyphenol compound can further improve the flame retardant properties of magnesium hydroxide as an inorganic flame retardant, so the limiting oxygen index is higher. Compared with Examples 5 to 7, Example 1 has better flame retardant properties. This may be because the synergistic flame retardant in Example 1 is red phosphorus. Compared with zinc borate, nano-montmorillonite, and calcium silicate in Examples 5 to 7, red phosphorus will decompose to produce phosphoric acid and polyphosphoric acid during combustion. These substances may react with antimony trioxide to form some more stable compounds such as antimony phosphate salts or polyphosphoric acid antimony salts. This compound has good thermal stability at high temperatures. Antimony phosphate salts have good thermal stability at high temperatures and can be used as part of the carbon layer to enhance the oxidation resistance and thermal decomposition resistance of the carbon layer. Polyphosphoric acid antimony salts can form a more stable carbon layer at high temperatures because they can form cross-links with carbon atoms in the carbon layer to increase the mechanical strength and durability of the carbon layer. The formed antimony phosphate salts and polyphosphoric acid antimony salts can be used as crosslinkers for the carbon layer. By forming chemical bonds with carbon atoms in the carbon layer, the overall structure of the carbon layer is enhanced, making it more difficult to be destroyed at high temperatures. Antimony phosphate salts and polyphosphoric acid antimony salts have good oxidation resistance. They can capture free radicals in the carbon layer to prevent further oxidation of the carbon layer, thereby protecting the material from flame erosion. Antimony trioxide plays a catalytic role in the formation of the carbon layer, promoting the polymerization of phosphoric acid and polyphosphoric acid to form a more complex phosphate structure, which plays a skeleton role in the carbon layer and enhances the stability of the carbon layer. Zinc borate, nano-montmorillonite, and calcium silicate mainly enhance the formation and stability of the carbon layer through physical interaction, and the synergistic effect produced is not as good as that of Example 1. Therefore, the cable material of Example 1 has better flame retardancy.Compared with Example 1, in Example 8, diglycidyl ether is additionally added when modifying the magnesium hydroxide. This may be because the introduction of diglycidyl ether can form a cross-linked structure to improve the dispersibility of the magnesium hydroxide and the strength of the matrix. The cross-linking effect can not only reduce the agglomeration tendency of the filler and make the flame retardant more evenly distributed, but also promote the formation of a dense carbonized layer during the combustion process, effectively blocking the diffusion of flame and oxygen, thereby indirectly improving the flame retardant properties and oxygen index of the material, resulting in better flame retardant properties of Example 8 than in Example 1.

[0081] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A waterproof and flame-retardant cable material, characterized in that: The invention comprises the following components in parts by weight: 80-110 parts of polyethylene, 10-30 parts of modified magnesium hydroxide, 40-60 parts of talc, 1-2 parts of antimony trioxide, 4-6 parts of synergistic flame retardant, 35-45 parts of heavy calcium carbonate, 15-25 parts of carbon black, 3-6 parts of antioxidant, 2-6 parts of plasticizer and 1-5 parts of lubricant.

2. The waterproof and flame-retardant cable material according to claim 1, characterized in that: The preparation method of the modified magnesium hydroxide comprises the following steps: X1. Mix terephthalaldehyde, 2,5-didodecylphenol and p-toluenesulfonic acid, heat and stir for 2-3 hours, cool to room temperature, add water and ethanol to produce precipitation, stir for 4-8 hours and filter, dry the filter cake and mix with acetic anhydride and sulfuric acid, stir at 60-70°C for 4-6 hours, cool and add water to produce precipitation, filter, and dry the filter cake to obtain a polyester compound; X2. Add magnesium hydroxide to ethanol and disperse it evenly. Then add the ethanol solution of the polyester compound. The mass ratio of magnesium hydroxide to the polyester compound is 1:2-3. After stirring, ultrasonic irradiation is performed, and the modified magnesium hydroxide is obtained by filtering and washing.

3. The waterproof and flame-retardant cable material according to claim 2, characterized in that: The molar ratio of terephthalaldehyde to 2,5-didodecylphenol and p-toluenesulfonic acid is 1:4-5:0.1-0.

2.

4. The waterproof and flame-retardant cable material according to claim 2, characterized in that: The temperature range of the heating in step X1 is 80-90°C.

5. The waterproof and flame-retardant cable material according to claim 2, characterized in that: The molar ratio of the filter cake to acetic anhydride and sulfuric acid after drying is 1:5-10:0.1-0.

2.

6. The waterproof and flame-retardant cable material according to claim 2, characterized in that: The concentration of the polyester compound ethanol solution is 1 to 5 wt %.

7. The waterproof and flame-retardant cable material according to claim 1, characterized in that: The synergistic flame retardant is one of zinc borate, nano-montmorillonite, silicate and red phosphorus.

8. The waterproof and flame-retardant cable material according to claim 1, characterized in that: The antioxidant is one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, 4,4'-bis(α,α-dimethylbenzyl) diphenylamine or 2,2,4-trimethyl-1,2-dihydroquinoline polymer.

9. The waterproof and flame-retardant cable material according to claim 1, characterized in that: The plasticizer is one of phthalic acid ester, aliphatic dibasic acid ester and polyol ester; the lubricant is one of stearic acid, paraffin, polyethylene wax and zinc stearate.

10. A method for preparing the waterproof and flame-retardant cable material according to any one of claims 1 to 9, characterized in that: The steps include: The components in the formula are blended, fully mixed, melt blended and then extruded and granulated to obtain the waterproof and flame-retardant cable material.

Citation Information

Patent Citations

  • Waterproof flame-retardant cable material and preparation method thereof

    CN106519521A

  • Low-density flame-retardant polyethylene cable material

    CN103374165A

  • Cable fiber communication line

    CN105440474A

  • Low-shrinkage phenolic moulding plastic and preparation method thereof

    CN116285207A

  • High-oxygen-index PVC cable material and preparation method thereof

    CN117343450A